Radiocarbon age and chronology of sediment core SK-312/12, along with Magnesium/Calcium and δ^1?O measurements on Trilobatus sacculifer (w/s), and paleotemperature and paleosalinity records - Sanjit Kumar Jena; Ravi Bhushan; Partha S Jena; Nisha Bharti; A K Sudheer; Prasanta Sanyal; Ajay Shivam; Ankur Dhabi (PANGAEA, 2025)
Sediment core SK-312/12 was collected from the Equatorial Indian Ocean at 3750m b.s.l.. Radiocarbon age-depth profile was continuous up to 70 cm of the core length. The core was sampled at each 1 cm interval. Nearly alternate sections were processed to separate foraminiferal carbonates from the bulk sediment. Radiocarbon ages were obtained from radiocarbon dating of mixed-layer species Globigerinoides ruber and Trilobatus sacculifer taken in sub-equal amounts from 250-425μm size fraction. The radiocarbon ages were calibrated with respect to the MARINE20 Calibration curve (Heaton et al., 2020) with a modern reservoir age (ΔR) of -54 + 65 yr (Dutta et al., 2001; Southon et al., 2002) under the R package "Bacon" (Blaauw & Christeny, 2011), and the Bayesian chronology was obtained. Stable oxygen isotopic analysis was carried out using 50-100μg of Trilobatus sacculifer (w/s) (250-355μm) shells from individual sample sections. Mg/Ca analysis of Trilobatus sacculifer (w/s) (250-355μm) was carried out following the cleaning protocol developed by Barker et al. 2003, the method for foraminiferal Mg/Ca analysis. Paleotemperature was reconstructed using the equation: Mg/Ca (mmol/mol) = 0.24 * exp(0.097T), given by Hollstein et al., 2017. The seawater oxygen isotopic record was obtained using the equation: T (?C) = 17 – 4.52 (δ18Ocarb - δ18Osw) + 0.03 (δ18Ocarb - δ18Osw)2, given by Erez & Luz, 1983. Paleosalinity was reconstructed using the equation: δ18Osw (VSMOW) = -8.89 + 0.27 * Ssw, given by Srivastava et al., 2007.